Clinical and Socioeconomic Differences in Methamphetamine-Positive Burn Patients - Solomon, Eve A (J Burn Care Res, 2019)
Previous research on burn patients who test positive for methamphetamines (meth) has yielded mixed results regarding whether meth-positive status leads to worse outcomes and longer hospitalizations. We hypothesized that meth-positive patients at our regional burn center would have worse outcomes. We reviewed burn admissions from January 2014 to December 2017 and compared total patients versus meth-positive, and matched meth-negative versus meth-positive for total BSA burn, length of stay (LOS), intensive care unit (ICU) days, days on ventilator, discharge status (lived/died), number of operating room (OR) visits, number of procedures, socioeconomic status, comorbidities, and discharge disposition. Of 1363 total patients, 264 (19.4%) were meth-positive on toxicology screen. We matched 193 meth-positive patients with meth-negative controls based on TBSA burn, age, and inhalation injury. In the total population comparison, meth-positive patients had larger burns (15.6% vs 12.2%; P = .004), longer LOS (17.8 vs 14.3 days; P = .041), and fewer operations/TBSA (0.12 vs 0.2; P = .04), and lower socioeconomic status. Meth-positive patients were less likely to be discharged to a skilled nursing facility, and more likely to leave against medical advice. In the matched patients, we found no significant differences in LOS or OR visits/TBSA burn. Meth-positive patients have lower socioeconomic status, larger burns, and longer LOS compared to the total burn population. Methamphetamine use, by itself, does not appear to change outcomes. Methamphetamine use leads to larger burns in a population with fewer resources than the general population.